(untitled) (Revista Brasileira Multidisciplinar, 2021)
The constant or repeated unprotected exposure to solar radiation can result in the onset of various harmful effects, such as inflammation, genetic mutation and hyperpigmentation, even than previous photoaging. The use of photoprotective formulations is one of the most effective tools to avoid this. However, most of the UV filters are unstable to UV radiation, can even permeate the skin and cause hepatotoxic effects. The aim of this study was to assess the efficacy and safety of a innovative sunscreen substance (E) -4- (tert-butyl) -N ’- ((E) -3- (4-methoxyphenyl) allylidene) benzhydrazide. Methodology: The sunscreen formulation containing the innovative substance was subjected to various stress conditions: 45±2° C, 5±2° C and exposure to sunlight. These samples were evaluated in relation to its rheology, pH, viscosity, density and SPF to determine its stability. The assessment of TBMAB release from the formulation was performed in Microette equipment. Hepatoma cells (HepG2) were used to determine the TBMAB cytotoxicity. Results and Discussion: In the stability study, no significant changes were observed in the formulation. The maximum concentration of TBMAB released from the formulation was 3.63 µg.cm-2. Also, it was evident the cytotoxic effect on the concentrations well above 3.63 µg.cm-2,displaying the safety of this substance, considering HepG2 cells. Conclusion: These results demonstrate that TBMAB is a suitable innovative substance to be used in suscreens, exhibiting stability, desired SPF value and safety, considering HepG2 cells. Thus, it could be a new alternative to prevent skin cancer.